Risk Factors for Hypertension in Hospitalised Patient Mortality with Laboratory-Confirmed SARS-CoV-2: A Population-Based Study in Limpopo Province, South Africa - Peter M. Mphekgwana; Sogo F. Matlala; Takalani G. Tshitangano; Naledzani J. Ramalivhana; Musa E. Sono-Setati (Journal of Respiration, 2022)
The coronavirus disease (COVID-19) pandemic has recently impacted and destabilised the global community. The healthcare systems of many countries have been reported to be partially or entirely interrupted. More than half of the countries surveyed (53%) have partially or completely disrupted hypertension treatment services. A population-based retrospective cohort study approach was used to determine the prevalence of hypertension and related risk factors for mortality in COVID-19 hospitalised patients in the Limpopo Province, South Africa. Hierarchical logistic regression was applied to determine the determinants of hypertension. Sixty-nine percent (69%) of mortality among individuals with laboratory-confirmed SARS-CoV-2 were elderly persons aged 60 years and above admitted to a person under investigation (PUI) ward (52%), and 66% had hypertension. Among the hospitalised COVID-19 patients who died, prominent risk factors for hypertension were advanced age, the presence of co-morbidities, such as diabetes and HIV/AIDS. There was no evidence to establish a link between hypertension and COVID-19 case severity. More cohort and systematic studies are needed to determine whether there is a link between hypertension and COVID-19 case severity.